Does natriuretic peptide monitoring improve outcomes in heart failure patients? A systematic review and meta-analysis. (15th July 2018) - Khan, Muhammad Shahzeb; Siddiqi, Tariq Jamal; Usman, Muhammad Shariq; Sreenivasan, Jayakumar; Fugar, Setri; Riaz, Haris; Murad, M.H.; Mookadam, Farouk; Figueredo, Vincent M.
Abstract: Background: Current guidelines do not support the use of serial natriuretic peptide (NP) monitoring for heart failure with preserved (HFpEF) or reduced ejection fraction (HFrEF) treatment, despite some studies showing benefit. We conducted an updated meta-analysis to address whether medical therapy in HFpEF or HFrEF should be titrated according to NP levels. Methods: MEDLINE, Scopus and Cochrane CENTRAL databases were searched for randomized controlled trials (RCTs) comparing NP versus guideline directed titration in HF patients through December 2017. The key outcomes of interest were mortality, HF hospitalizations and all-cause hospitalizations. Risk ratios and 95% confidence intervals were pooled using random effects model. Sub-group analyses were performed for type of NP used, average age and acute or chronic HF. Results: Eighteen trials including 5116 patients were included. Meta-analysis showed no significant difference between the NP-guided arm versus guideline directed titration in all-cause mortality (RR = 0.91 [0.81, 1.03]; p  = 0.13), HF hospitalizations (RR = 0.81 [0.65, 1.01]; p  = 0.06), and all cause hospitalizations (RR = 0.93 [0.86, 1.01]; p  = 0.09). The results were consistent upon subgroup analysis by biomarker type (NT-proBNP or BNP) and type of heart failure (acute or chronic and HFrEF or HFpEF). Sub-group analysis suggested that NP-guided treatment was associated with decreased all-cause hospitalizations in patients younger than 72 years of age. Conclusion: The available evidence suggests that NP-guided therapy provides no additional benefit over guideline directed therapy in terms of all-cause mortality and HF-related hospitalizations in acute or chronic HF patients, regardless of their ejection fraction. Highlights: Overall, NP-guided therapy provides no additional decrease in mortality. This result was consistent in both the BNP and NT-proBNP subgroups. The same was observed in both the Acute HF and Chronic HF subgroups. Efficacy of NP-guided therapy when implemented by non-specialists is understudied.